The perils of Taylor Rules - Jess Benhabib; Stephanie Schmitt-Grohe; Martin Uribe (Rutgers University, Department of Economics, 1998)
Since John Taylor's (1993) seminal paper, a large literature has argued that active interest rate feedback rules, that is, rules that respond to increases in inflation with a more than one-for-one increase in the nominal interest rate, are stabilizing. In this paper, we argue that once the zero bound on nominal interest rates is taken into account, active interest-rate feedback rules can easily lead to unexpected consequences. Specifically, in the context of a sticky-price model, we show that even if the steady state at which monetary policy is active is locally the unique equilibrium, typically there exists an infinite number of equilibrium trajectories originating arbitrarily close to that steady state that converge either to another steady state at which monetary policy is passive or to a stable limit cycle around the active steady state. We conclude that the use of local techniques for monetary policy evaluation might lead to spurious policy recommendations.
Keywords: E31; E52; E63; 330; Interest rate feedback rules; liquidity traps; multiple equilibria; zero bound on nominal rates